Oligo-Carrageenans Stimulate Growth by Enhancing Photosynthesis, Basal Metabolism, and Cell Cycle in Tobacco Plants (Var. Burley) - Moenne-Munoz, A; Gonzalez-Figueroa, A (2012)
Sin Editorial Disponible